Rotatory Knee Laxity Exists on a Continuum in Anterior Cruciate Ligament Injury. (5th February 2020) - Lian, Jayson; Diermeier, Theresa; Meghpara, Mitchell; Popchak, Adam; Smith, Clair N.; Kuroda, Ryosuke; Zaffagnini, Stefano; Samuelsson, Kristian; Karlsson, Jón; Irrgang, James J.; Musahl, Volker; Sheean, Andrew J.; et al.
Abstract : Background: The purpose of this investigation was to compare the magnitude of rotatory knee laxity in patients with a partial anterior cruciate ligament (ACL) tear, those with a complete ACL tear, and those who had undergone a failed ACL reconstruction. It was hypothesized that rotatory knee laxity would increase with increasing injury grade, with knees with partial ACL tears demonstrating the lowest rotatory laxity and knees that had undergone failed ACL reconstruction demonstrating the highest rotatory laxity. Methods: A prospective multicenter study cohort of 354 patients who had undergone ACL reconstruction between 2012 and 2018 was examined. All patients had both injured and contralateral healthy knees evaluated using standardized, preoperative quantitative pivot shift testing, determined by a validated, image-based tablet software application and a surface-mounted accelerometer. Quantitative pivot shift was compared with the contralateral healthy knee in 20 patients with partial ACL tears, 257 patients with complete ACL tears, and 27 patients who had undergone a failed ACL reconstruction. Comparisons were made using 1-way analysis of variance (ANOVA) with post hoc 2-sample t tests with Bonferroni correction. Significance was set at p < 0.05. Results: There were stepwise increases in side-to-side differences in quantitative pivot shift in terms of lateral knee compartment translation for patients with partial ACL tears (mean [and standard deviation], 1.4 ± 1.5 mm), those with complete ACL tears (2.5 ± 2.1 mm), and those who had undergone failed ACL reconstruction (3.3 ± 1.9 mm) (p = 0.01) and increases in terms of lateral compartment acceleration for patients with partial ACL tears (0.7 ± 1.4 m/s 2 ), those with complete ACL tears (2.3 ± 3.1 m/s 2 ), and those who had undergone failed ACL reconstruction (2.4 ± 5.5 m/s 2 ) (p = 0.01). A significant difference in lateral knee compartment translation was found when comparing patients with partial ACL tears and those with complete ACL tears (1.2 ± 2.1 mm [95% confidence interval (CI), 0.2 to 2.1 mm]; p = 0.02) and patients with partial ACL tears and those who had undergone failed ACL reconstruction (1.9 ± 1.7 mm [95% CI, 0.8 to 2.9 mm]; p = 0.001), but not when comparing patients with complete ACL tears and those who had undergone failed ACL reconstruction (0.8 ± 2.1 [95% CI, −0.1 to 1.6 mm]; p = 0.09). Increased lateral compartment acceleration was found when comparing patients with partial ACL tears and those with complete ACL tears (1.5 ± 3.0 m/s 2 [95% CI, 0.8 to 2.3 m/s 2 ]; p = 0.0002), but not when comparing patients with complete ACL tears and those who had undergone failed ACL reconstruction (0.1 ± 3.4 m/s 2 [95% CI, −2.2 to 2.4 m/s 2 ]; p = 0.93) or patients with partial ACL tears and those who had undergone failed ACL reconstruction (1.7 ± 4.2 m/s 2 [95% CI, −0.7 to 4.0 m/s 2 ]; p = 0.16). An increasing lateral compartment translation of the contralateral, ACL-healthy knee was found in patients with partial ACL tears (0.8 mm), those with complete ACL tears (1.2 mm), and those who had undergone failed ACL reconstruction (1.7 mm) (p < 0.05). Conclusions: A progressive increase in rotatory knee laxity, defined by side-to-side differences in quantitative pivot shift, was observed in patients with partial ACL tears, those with complete ACL tears, and those who had undergone failed ACL reconstruction. These results may be helpful when assessing outcomes and considering indications for the management of high-grade rotatory knee laxity. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.